THE HAND MEMORY - Calegari, Giulio (Design/Arts/Culture, 2023)
Traces of ancient gestures are recalled and re-interpreted in an artistic way. Prehistoric chipped stone artefacts: preserve techniques, gestures, sounds and memories. Maybe stories. Just like in a book or in a musical score. We can reconstruct these ancient artefacts and use them to verify their function.